AN ARTICLE BY SCIENTIST WOLFRAM ERBERHARD ABOUT THE KYRGYZ (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Most of the history of the Kyrgyz people lies in Chinese sources. However, since the 19th century, Western scholars have learned the ancient Chinese language, had access to Chinese archives and were able to read hundreds of ancient Chinese sources. Therefore, Western studies such as Chinese sources are very important for Kyrgyz history. One of the Western scientists is German sinologist Wolfram Erberhard. He learned the ancient Chinese language, read many ancient sources, wrote works on Chinese history and the history of Turkic peoples, and made great contributions to the world of science. His works were published in German, English and Turkish and translated into other languages. Unfortunately, his works were not known to our society because they were not translated into Russian or Kyrgyz. Because he provided information about the ancient Turkic peoples, including the Kyrgyz, based on ancient Chinese sources. In this article, in addition to providing information about Wolfram Erberhard’s short biography, we will try to translate the “Kyrgyz” chapter in his work and bring it to the Kyrgyz scientific world.
Keywords: Erberhard, Kyrgyz, Chinese sources, history of Kyrgyz, works on Kyrgyz